Implementasi manajemen risiko terhadap keberlangsungan usaha pada umkm batik - Puspita, Ririnn Diyah (Maliki Interdisciplinary Journal, 2025)
The COVID-19 pandemic has significantly impacted the continuity of businesses, particularly for Micro, Small, and Medium Enterprises (SMEs). One of the sectors most affected is the batik industry. This paper discusses implementing risk management in Batik SMEs with the primary focus is operational, legal, reputational, and strategic risks that could threaten the business’s sustainability. Using the ISO 31000 framework, this study identifies and assesses the risks faced by Batik SMEs and provides mitigation recommendations to ensure business continuity. The results indicate that effective risk management can help SMEs survive and adapt to the changes brought about by the pandemic. Effective risk management not only helps MSMEs face external challenges such as market changes and regulations, but also increases the resilience and resilience of their businesses in the long term.